The effect of using fermented lime (Citrus aurantifolia) waste powder (FLWP) on performance, lymphoid organs, and heterophil/lymphocyte ratio of broiler chickens - Hanna Dzawish Shihah; Dwi Sunarti; Sri Sumarsih (Universitas Sebelas Maret, 2021)
Objective: Fermented lime waste had potential value as a feed additive for poultry. A Bioactive compound such as citric acid in the lime waste can improve the broiler's performance and body resistance. The study purposed to evaluate the effect of using fermented lime waste powder (FLWP) on the broiler performance and body resistance.Methods: This study used 200 female broiler strain Lohman MB 202 chickens. The research design used a completely randomized design with four treatment levels of fermented lime waste powder (FLWP) by 0%, 1%, 2%, and 3% in every rations with each treatment replicated five times. The parameters observed are feed intake, feed conversion ratio, final body weight, carcass percentage, abdominal fat percentage, lymphoid organ’s relative weight, and heterophil/lymphocyte ratio (H/L ratio). Data were calculated using the analysis of variance and difference test with Duncan's Multiple Range Test. Data analysis were calculated using the SPSS 19.0 program.Results: The result indicates that using FLWP improved (p<0.05) the relative weight of the Bursa of fabricius at T0 0.11%; T1 0.19%; T2 0.19%; and T3 0.17% respectively. The FLWP at 3% level improved (p<0.05) broiler chicken’s H/L ratio. Performance, carcass percentage, and abdominal fat percentage among treatments were not influenced (p>0.05) by FLWP addition.Conclusions: It concludes that adding FLWP at a 1% level increases the relative weight of Bursa of fabricius (0.17-0.19%) without depressed performance of broiler.